In vitro immunomodulation of splenocytes from DO11.10 mice by the food colouring agent amaranth. (December 2017) - Lefebvre, David E.; Ross, Nikia; Kocmarek, Andrea L.; Cowell, Simon; Dai, Shelley; Qiao, Cunye; Curran, Ivan; Koerner, Terry; Bondy, Genevieve S.; Fine, Jason H.
Abstract: The chemical amaranth (AM) is permitted as a colouring agent in a variety of foods. Safety was established based on chronic rodent studies. AM and its metabolite naphthionic acid (NA) can be absorbed through the intestine, exposing circulating immune cells including splenocytes. An AM feeding study in rats demonstrated an increase in blood lymphocytes. Yet, in contrast, AM inhibited the delayed-type hypersensitivity reaction to antigen. DO11.10 mice express a T Cell Receptor specific for ovalbumin323-339 peptide (OVAp) presented by I-A d MHCII. DO11.10 splenocytes were cultured to evaluate mechanisms by which AM and NA modulate immune cell function in vitro . Exposure to OVAp alone for 72 h induced cell proliferation, and combination with 2 or 20 μg/mL AM increased IFN-γ. Cytotoxicity was evident at higher concentrations of AM (200 and 2000 μg/mL) and NA (2000 μg/mL) in combination with OVAp, as both cell number and cytokine secretion decreased. At 200 μg/mL AM with OVAp, immunotoxicity gene expression was modified and OVAp-specific KJ1-26 + CD28 + cells became enriched. The equivalent dose of NA did not modify those parameters. Using an antigen-specific model in vitro, lower concentrations of AM potentiated pro-inflammatory cytokine production, and higher concentrations of AM and NA demonstrated cytotoxicity. Highlights: Amaranth potentiated pro-inflammatory interferon-gamma from spleen immune cells during their response to ovalbumin antigen. At higher concentrations amaranth and a metabolite were cytotoxic to the cell mixture and inhibited the cytokine response. In parallel at higher amaranth concentrations cells expressing an ovalbumin-specific T Cell Receptor became enriched.